EARLY LIFE AND EDUCATION OF THE BRONTE SISTERS (International journal of artificial intelligence, 2025)
The Bronte sisters, Charlotte, Emily, and Anne, were born in the early 19th century in the small village of Thornton, Yorkshire, England. Their father, Patrick Bronte, was a clergyman and their mother, Maria Branwell, died when the girls were young. The siblings were very close and spent much of their childhood creating imaginary worlds and writing stories together. They were also avid readers and were educated at home by their father, who encouraged their love of literature.